ANALISIS PERBEDAAN RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH KEJADIAN PEMECAHAN SAHAM (STOCK SPLIT) TAHUN 2017 (Studi Empiris Pada Perusahaan Go Public Yang Terdaftar di Bursa Efek Indonesia) - Nanda Adhiwijaya; Sri Hermuningsih; Mujino Mujino (JURNAL EKOBIS DEWANTARA, 2018)
ABSTRACT The purpose of this study is to determine whether there is (1) the effect of stock split event on stock return before, during and after and (2) trading volume of stock before, during and after on company listed in Indonesia Stock Exchange (BEI) in 2017. In this research classified type of quantitative research. The population is all companies listed in Indonesia Stock Exchange in 2017. The sample of research is 2 companies in different sectors: (1) PT. Indal Aluminium Industry Tbk (INAI),(2) PT. Surya Esa Perkasa Tbk (ESSA). Data collection method using documentation method, while technique of data analysis using different test that is T test (T-test). The result of the research shows that stock return test in the period before with after Stock Split event is known that sig. 0,179 which means not proven, stock return in the period before with the time of Stock Split event known that sig. 0,000 which means proven and stock returns in the current period with after Stock Split event known sig. 0,000 which means proven. From the test results of trading volume of shares in the period before with after the event of Stock Split known that sig. 0,009 which means proven. In the period before the time of Stock Spli event is known that sig. 0,000 which means proven and in the period when after the Stock Split event is known that sig. 0,007 means proven. Keywords: stock return, stock trading volume and stock split event.